De l’espace à l’aspect : les bases ontologiques des procès de déplacement - Michel Aurnague (Corela)
In the linguistic literature, verbs denoting manner of motion have been frequently opposed to verbs of strict or inherent motion. However, the characterization of the latter class of predicates is often problematic, be it because it is based on inaccurate spatial or spatio-temporal concepts or because it directly resorts to the aspectual properties (inner aspect) of the verbs. In this paper, we first propose to categorize motion eventualities on the basis of the concepts of change of basic locative relation (Boons 1987) and of change of placement. After going through the main advantages of such an approach, we focus on the verbs which combine both notions (strict motion events) and show how their aspectual properties can be deduced from their spatio-temporal structure.